Review of Angeliki Spiropoulou’s Virginia Woolf, Modernity and History: Constellations with Walter Benjamin - Funke, Jana (Historein, 2013)
Review of Angeliki Spiropoulou’s Virginia Woolf, Modernity and History: Constellations with Walter Benjamin